Caesarean delivery: conflicting interests. Issue 6 (December 2015) - Osuna, Eduardo; Pérez Cárceles, Maria Dolores; Sánchez Ferrer, Maria Luisa; Machado, Francisco
Abstract: Within the maternal–fetal relationship, interests may sometimes diverge. In this paper, a pregnant woman's refusal to undergo a caesarean delivery, which was recommended both to save the life of the fetus and to minimize risks to her, is described. The legal aspects involved in the conflict between maternal autonomy and fetal well-being are analysed. The patient requested an abortion because of the poor condition of the fetus; however, according to Spanish legislation, the possibility of abortion was rejected as the pregnancy was in its 27th week. The woman still persisted in her refusal to accept a caesarian delivery. After the medical team sought guidance on the course to follow, the Duty Court authorized a caesarean delivery against the wishes of the patient. From a legal point of view, at stake were the freedom of the woman – expressed by the decision to reject a caesarean delivery – and the life of the unborn child. In clinical treatment, the interests of the fetus are generally aligned with those of the pregnant woman. When they are not, it is the pregnant woman's autonomy that should be respected, and coercion should form no part of treatment, contrary to the decision of this court.